Life-cycle equilibrium unemployment - Arnaud Chéron; Jean-Olivier Hairault; François Langot (Institute for the Study of Labor (IZA), 2008)
This paper develops a life-cycle approach to equilibrium unemployment. Workers only differ respectively to their distance from deterministic retirement. A non age-directed search equilibrium is then typically featured by increasing (decreasing) firing (hiring) rates with age and a hump-shaped age profile for employment. Because of intergenerational inefficiencies, the Hosios condition no longer achieves efficiency. We then explore the optimal age-pattern of some policy tools to restore this efficiency. The optimal profile for employment subsidies should increase with age, whereas firing taxes and hirings subsidies would have to be hump-shaped. Lastly, we examine the robustness of our results. We show that age-directed recruitment policies cannot exist in equilibrium even if it would have been ex-ante possible, and that introducing endogenous search effort of unemployed workers reinforces our main results.
urn:nbn:de:101:1-2008031807
Keywords: J22; 330; Job search; matching; life cycle; Theorie der Arbeitslosigkeit; Lebenszyklus; Arbeitsuche; Arbeitsnachfrage; Matching; Arbeitsmarktpolitik; Altersgruppe; Theorie; OECD-Staaten